2018
DOI: 10.5144/0256-4947.2018.288
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of confidence among Saudi nursing interns during internship program: a cross-sectional study

Abstract: BACKGROUNDSaudi nursing students are trained in theoretical and clinical nursing competencies for four years before transition to newly graduated nurses through a one-year internship program. The transition period is crucial as nursing students have low confidence without adequate clinical experience.OBJECTIVESValidate and culturally adapt the Arabic version of the Self-Efficacy for Clinical Evaluation Scale (SECS) and explore nursing interns perceived confidence (self-efficacy).DESIGNCross-sectional.SETTINGFo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
(21 reference statements)
3
14
0
Order By: Relevance
“…A cross-sectional study was carried out by Asboshiqaha et al, [12], to investigate the validity of a clinical training program in Saudi Hospitals. The included hospital for the study was Tertiary Hospital in Riyadh, Saudi Arabia.…”
Section: Impact Of Hfs On Self-confidencementioning
confidence: 99%
See 3 more Smart Citations
“…A cross-sectional study was carried out by Asboshiqaha et al, [12], to investigate the validity of a clinical training program in Saudi Hospitals. The included hospital for the study was Tertiary Hospital in Riyadh, Saudi Arabia.…”
Section: Impact Of Hfs On Self-confidencementioning
confidence: 99%
“…The included hospital for the study was Tertiary Hospital in Riyadh, Saudi Arabia. Student's completed their clinical experience between October 2016 and March 2017 and included 300 students [12]. There was a survey study in which the validity and cultural adaptation of the "Self-Efficacy for Clinical Evaluation Scale (SECS) [12]," which is an Arabic version of selfefficacy training program instrument was studied and verified.…”
Section: Impact Of Hfs On Self-confidencementioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, a descriptive cross-sectional study was conducted among 300 Saudi nursing interns to validate and measures cultural adapt the Arabic version of self-efficacy for clinical evaluation scale (SECE) and explore nursing interns' perceived confidence. The study found that the Arabic version of SECS was successfully cross-culturally adapted to reveal that gender, duration of internship, and place of training affected the perceptions of the Saudi nursing interns regarding self-efficacy [9]. In this way, the instrument could help preceptors formulate more appropriate strategies for enhancing nursing intern competence and promoting their self-efficacy as they transition to the role of registered nurse [9].…”
Section: Introductionmentioning
confidence: 99%